A dashboard of populations and tourists for year 2019 - 2022 in Malaysia using GIS application / Liyana Nadia Hafize and Batrisyia Damia Hasbullah - Hafize, Liyana Nadia; Hasbullah, Batrisyia Damia (Universiti Teknologi MARA (UiTM), 2024)
"A Dashboard of Populations and Tourists for Year 2019 - 2022 in Malaysia Using GIS Application," the project's final year title, presents an interactive and thorough dashboard created with ArcGIS Pro and ArcGIS Dashboards. The study addresses the challenges of scattered and inaccessible data related to population density and tourist influx across various states in Malaysia from 2019 to 2022. The project improves data visualization and analytical skills, enabling improved decision-making for sustainable development and urban planning, by combining both non-spatial and spatial data into one intuitive dashboard.